Analysis of Sildenafil Citrate in Male Stamina Supplements with Densitometry TLC Method - Sugijanto . (Journal of Global Pharma Technology, 2016)
Introduction: Sildenafil citrate is a chemical drug that is prohibited by Indonesia National Agency of Drug and Food Control to being added in male stamina supplements. Recently, several male health supplements have been found to contain sildenafil citrate. Objection: The purpose of this study was to validate the TLC-densitometry method used in the quantitative analysis of sildenafil citrate. Methods: Validation of the method determined is selectivity, detection limit, quantitation limit, linearity, accuracy, and precision. A good solvent for extracting sildenafil citrate from the matrix sample is methanol. Sildenafil citrate was separated from the matrix component in silica gel F254 using methanol: ethyl acetate (1: 2) as an eluent. The retardation factor of sildenafil citrate is 0.41, the resoluteion factor between sildenafil citrate and the closest matrix compound is 3.0. The response is linear in the range of sildenafil citrate concentrations 500 - 1500 ppm. A good solvent for extracting sildenafil citrate from the matrix sample is methanol. Results: The results showed that the detection limit of sildenafil citrate was 4.96 and the quantization limit was 15.03 ppm. Sildenafil citrate recovery was found 98.46-101.09% with an average of 99.83% and precision results of 0.99%. Conclusion: The Densitometry TLC method can be used for quantitative analysis of sildenafil citrate because the validation parameters have met the requirements.Keywords: Sildenafil Citrate, TLC-Densitometry, Validation method.